Comanche Marker Trees of Texas - Houser, Steve, 1959-; Arterberry, Jimmy W., 1961-; Pelon, Linda (Book collections on Project MUSE., 2016)
In this unprecedented effort to gather and share knowledge of the Native American practice of creating, designating, and making use of marker trees, an arborist, an anthropologist, and a Comanche tribal officer have merged their wisdom, research, and years of personal experience to create Comanche Marker Trees of Texas. A genuine marker tree is a rare find-only six of these natural and cultural treasures have been officially documented in Texas and recognized by the Comanche Nation. The latter third of the book highlights the characteristics of these six marker trees and gives an up-to-date hi.